Analysis of abnormal returns and trading volume activity before and after the announcement of the implementation of new normal - Pande I Komang Juniantara; Ni Made Ayu Dwijayanti; Putu Adi Suprapto (Journal of Applied Sciences in Accounting, Finance, and Tax, 2023)
The announcement of the New Normal implementation on June 1, 2020 is anticipated to serve as a pivotal moment poised to revitalize the previously sluggish Indonesian Capital Market during the COVID-19 Pandemic. The purpose of this study was to see whether there were differences in abnormal returns and trading volume activity between before and after the announcement of the implementation of the New Normal in Indonesia. This type of research is comparative quantitative research with an event study approach in hotel, restaurant and tourism companies. The population in this research is all company shares listed on the Indonesian capital market until 2020, totaling 711 company shares. The sample selection used purposive sampling, resulting in a research sample of 37 company shares. The observation period was carried out for 15 days, namely 7 days before, 7 days after, and 1 day of the New Normal event in Indonesia. The analysis technique uses Descriptive Statistics Test, Normality Test and Hypothesis Test. The results of the study show that there is no significant difference in abnormal returns and trading volume activity between before and after the announcement of the implementation of the New Normal in Indonesia. This proves that there is still information asymmetry between market participants regarding the announcement of the implementation of the New Normal in Indonesia which causes the market not to react to this event.